2018
DOI: 10.1002/cjce.23205
|View full text |Cite
|
Sign up to set email alerts
|

Surface treatment with amino acids of porous collagen based scaffolds to improve cell adhesion and proliferation

Abstract: The purpose of this study was to improve the biocompatibility of glutaraldehyde (GA) cross‐linked chitosan coated collagen scaffold for cartilage tissue regeneration. In order to prevent the potential toxicity of GA, we treated the designed scaffold with either glutamic acid or glycine. Amino acid treated scaffolds were characterized by scanning electron microscopy (SEM) techniques. Afterward, chondrocyte interaction with the composite scaffold was investigated assessing cell adhesion and proliferation using H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…These findings clearly implied the enhancement of cell proliferation attributes to the effects of collagen on cell viability. In short, these findings clearly demonstrated the process of incorporating collagen layer on the scaffold is an efficient way to initiate cell attachment and supports cell growth [63,64]. (a) Figure 7.…”
Section: Evaluation Of Cell Proliferation Of Fibroblast Cells On Scaffoldsmentioning
confidence: 75%
See 1 more Smart Citation
“…These findings clearly implied the enhancement of cell proliferation attributes to the effects of collagen on cell viability. In short, these findings clearly demonstrated the process of incorporating collagen layer on the scaffold is an efficient way to initiate cell attachment and supports cell growth [63,64]. (a) Figure 7.…”
Section: Evaluation Of Cell Proliferation Of Fibroblast Cells On Scaffoldsmentioning
confidence: 75%
“…Additionally, the collagen peptide coating enhanced the surface wettability of sample scaffolds. The significant hydrophilicity enhancing effect of collagen peptide could be associated with the amino groups in collagen [64,65].…”
Section: Hydrophilicity Of Fabricated Scaffoldsmentioning
confidence: 99%
“…As part of an effort to improve the biocompatibility of glutaraldehyde-crosslinked chitosan-coated collagen scaffolds, Rouabhia et al added either glutamic acid or glycine to the scaffolds. [10] In vitro research has shown that amino acids improve chondrocyte adhesion and proliferation inside the scaffold pores, indicating better scaffold biocompatibility. Han et al established a double-layer collagen scaffold to regenerate cartilaginous lesions.…”
Section: Collagen and Gelatinmentioning
confidence: 99%
“…The emergence of cartilage tissue engineering (CTE) shows the prospect of being a potential alternative to osteochondral defect repair. Biomimetic materials currently used for cartilage tissue engineering include 3D porous scaffolds, [6] hydrogels, [7] electrospun scaffolds, [8] and microspheres, [9] and to improve the biological activity of materials, drugs, [10] bioactive factors, [11] and stem cells [12] can be added to these materials (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The first gathers contributions on industrially important catalysis applications and energy conversion (Fischer‐Tropsch synthesis, molybdenum carbide catalysis, coal pyrolysis and gasification, biorefinery transformations, carbon dioxide biomass gasification, and baffled fluidized and bubble column reactors). The second topic picked up a couple of biotechnology applications (enzyme immobilization on magnetic nanoparticles and cell adhesion on collagen scaffolds). The third one accrued agri‐food and plant valorization contributions (free‐radical anthocyanin oxidation, synthesis of agro‐based surfactants, rare‐earth toxicity in horticultural plants, and extraction of cereal wax‐like components).…”
mentioning
confidence: 99%